Measurement of Intact Serum Parathormone and Corrected Serum Calcium after Thyroid Surgery - Sweety Kumari; Rahul Khanna; Neeraj K. Agrawal; Ritika Khanna; Ram Niwas Meena (Annals of the National Academy of Medical Sciences (India), 2023)
Postoperative hypocalcemia is an important complication of thyroid surgery. The present study was undertaken to measure the serum levels of intact parathormone (iPTH) and corrected serum calcium (CSC) in the immediate postoperative period and then sequentially till 1 month after thyroid surgery. A total of 36 patients undergoing total thyroidectomy and 44 undergoing hemithyroidectomy had measurement of the level of iPTH and CSC at 1 hour, 1 day, 1 week, and 1 month after surgery. A mean drop of 9.3% in CSC, 40% in iPTH, and 10% in ionic calcium levels was noted 1 hour after total thyroidectomy. All the patients recovered to near preoperative levels at the 1-month follow-up. Among hemithyroidectomy patients, significant postsurgery drop in levels was not observed. The importance of the study is early recognition of a hypoparathyroid state at 1 hour after surgery and institution of calcium replacement, thereby sparing the patient from unpleasant symptoms of hypocalcemia. Furthermore, patients with a drop in the iPTH levels below the defined hypoparathyroidism levels should have careful evaluation of their thyroidectomy specimen for identification and possible autotransplantation of the parathyroid gland intraoperatively or in the immediate postoperative time frame.